HIGH TEMPERATURE OPERATION TO IMPROVE LITHIUM PLATING HOMOGENEITY IN ANODE-FREE LITHIUM BATTERY - Nur Hidayat, Hilmy
The increasing demand for high capacity batteries has driven the search for alternative anode materials. Lithium metal, with specific capacity more than ten times higher than that of graphite (3860 vs 372 mAh g-1) has been considered as a promising alternative, but its application is limited due to poor cycling stability and high reactivity. Anode-free lithium battery is a new design of lithium metal batteries which does not incorporate any active material when assembled. This battery is designed as a solution for the reactivity of lithium metal battteries. However, anode-free lithium battery has a low coulombic efficiency as a result of unstable solid electrolyte interface (SEI). Several strategies to increase the stability of anode-free lithium batteries have been investigated, such as electrolyte modification, current collector surface engineering, and modification of cycling protocol. This research focuses on studying the phenomena that occur in anode-free lithium batteries. The test will use carbonate electrolytes with two different salts: lithium hexafluorophosphate (LiPF6) and a combination of lithium difluoro(oxalato)borate (LiDFOB) and lithium tetrafluoroborate (LiBF4). Linear sweep voltammetry (LSV) tests reveal that the LiDFOB-LiBF4 has a higher oxidation stability (5.21 V) than LiPF6 (4.35 V). After that, galvanostatic charge-discharge tests for 30 cycles performed at 20°C and 40°C show that higher operating temperature led to increased battery stability. This is supported by electrochemical impedance spectroscopy (EIS) data which found an increase in SEI layer thickness inside batteries with LiDFOB-LiBF4 and at higher temperature. Visual observations also reveal that lithium plating on the copper current collector surface in LiDFOB-based electrolyte is more homogeneous. SEM images demonstrate that high temperature operation increases the particle size of the lithium deposition.